2019
DOI: 10.3390/en12234505
|View full text |Cite
|
Sign up to set email alerts
|

Management and Distribution Strategies for Dynamic Power in a Ship’s Micro-Grid System Based on Photovoltaic Cell, Diesel Generator, and Lithium Battery

Abstract: Combining new energy technology with electric propulsion technology is an effective way to decrease the pollution of water resources caused by cruise ships. This study examines the stable parallel operation of a ship’s micro-grid system through a dynamic power management strategy involving a step change in load. With cruise ships in mind, we construct a micro-grid system consisting of photovoltaics (PV), a diesel generator (DG), and a lithium battery and establish a corresponding simulation model. We then anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…At present, there are many manufacturers that have invested in technologies related to the development of automotive Lithium batteries so that the lithium battery industry can be more perfect [10,11]. Chang's Ascending Enterprise Company, Ltd. (CAEC, Taichung City, Taiwan), the upstream manufacturer of lithium batteries, in which the Formosa Plastics Group has invested, has been in the field of car battery layout for a long time [12]. Many middle-and down-stream manufacturers have also begun to transform, in an effort to not become absent from global supply chains [11][12][13].…”
Section: The Current Trends Of Lithium Battery Industries In China Anmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are many manufacturers that have invested in technologies related to the development of automotive Lithium batteries so that the lithium battery industry can be more perfect [10,11]. Chang's Ascending Enterprise Company, Ltd. (CAEC, Taichung City, Taiwan), the upstream manufacturer of lithium batteries, in which the Formosa Plastics Group has invested, has been in the field of car battery layout for a long time [12]. Many middle-and down-stream manufacturers have also begun to transform, in an effort to not become absent from global supply chains [11][12][13].…”
Section: The Current Trends Of Lithium Battery Industries In China Anmentioning
confidence: 99%
“…Chang's Ascending Enterprise Company, Ltd. (CAEC, Taichung City, Taiwan), the upstream manufacturer of lithium batteries, in which the Formosa Plastics Group has invested, has been in the field of car battery layout for a long time [12]. Many middle-and down-stream manufacturers have also begun to transform, in an effort to not become absent from global supply chains [11][12][13]. In summary, Chinese manufacturers are expected to focus on the placement strategy of the lithium battery market in the next few years, while Taiwanese manufacturers will mainly focus on a technology-oriented direction [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: The Current Trends Of Lithium Battery Industries In China Anmentioning
confidence: 99%
“…Yu et al, reported "Management and Distribution Strategies for Dynamic Power in a Ship's Micro-Grid System Based on Photovoltaic Cell, Diesel Generator, and Lithium Battery" [6]. This study examines the stable parallel operation of a ship's micro-grid system through a dynamic power management strategy involving a step change in load.…”
Section: The Topic Of Energies and Its Applicationsmentioning
confidence: 99%
“…Microgrids propitiate the integration of DERs, making power systems more efficient and providing a better management of energy resources [8], [9]. As regards its operation mode, a microgrid can operate connected to main grid or in islanded mode.…”
Section: Technologicalmentioning
confidence: 99%